Dampak Infeksi TORCH Intrauterin terhadap Perkembangan Janin dan Bayi: Tinjauan Literatur - Harlinda RA (Pusat Riset dan Inovasi Nasional, 2026)
TORCH infections (Toxoplasmosis, Other infections, Rubella, Cytomegalovirus, and Herpes simplex) during pregnancy represent a significant health problem that can have serious impacts on fetal and neonatal health. These infections have the potential to impair fetal growth and development and to cause various complications, both in the short and long term. Therefore, a comprehensive understanding of the clinical manifestations, diagnostic processes, and long-term consequences of TORCH infections is essential to ensure optimal management for pregnant women and their infants. This article discusses the wide range of clinical symptoms associated with TORCH infections, which are often nonspecific and thus pose particular challenges in diagnosis. In addition, it addresses difficulties in establishing an accurate diagnosis, available management options, and the potential long-term risks arising from these infections. TORCH infections are known to cause intrauterine growth restriction, neurological abnormalities, sensory impairments such as vision and hearing loss, and developmental delays in children. Early detection through prenatal screening and timely intervention are key factors in minimizing adverse outcomes. As one of the major risk factors during pregnancy, TORCH infections can contribute to various serious fetal complications with long-term consequences. Therefore, optimizing prenatal care, including routine examinations, early screening, and appropriate therapy, is crucial to reduce risks and improve maternal and neonatal health outcomes.